Association Between Workplace Bullying Occurrence and Trauma Symptoms Among Healthcare Professionals in Cyprus - Aristidou, Loukia; Mpouzika, Meropi; Papathanassoglou, Elizabeth; Middleton, Nicos; Karanikola, Maria (My University, 2020)
Workplace bullying/mobbing is an extreme work-related stressor, but also a severe hazard for physical, mental and psychological health in healthcare employees, including nurses. A range of trauma-related symptoms has been linked with bullying victimization. The aim of the study was the investigation of workplace bullying/mobbing-related trauma symptoms in Greek-Cypriot nurses working in emergency and critical care settings, as well as of potential correlations with demographic and occupational variables. A descriptive, cross-sectional correlational study was performed in a convenience sample of 113 nurses. A modified version of the Part B.CII of The Workplace Violence in the Health Sector-Country Case Studies Research Instrument (WVHS-CCSRI Part C.II-M) and the modified Secondary Traumatic Stress Scale (STSS-M) were used for the assessment of bullying/mobbing frequency and workplace bullying/mobbing-related trauma symptoms, respectively. A total of 46.9% of the sample reported experiences of both bullying/mobbing victimization and witnessing of bullying/mobbing to others (VWB subgroup), 21.2% reported solely bullying/mobbing victimization (SVB subgroup) and 10.6% reported witnessing of bullying/mobbing to others (SWB subgroup). A total of 22.3% did not experience or witness any bullying/mobbing at the workplace. Trauma symptoms intensity (STSS-M total score) was more severe in the participants a) with a high frequency of workplace bullying/mobbing experiences compared to those with a moderate frequency of such experiences (p = 0.018), b) of the VWB subgroup compared to those of the SWB subgroup (p = 0.019), c) employed in Emergency Departments compared to those employed in ICUs (p = 0.03), d) who had considered resigning due to bullying/mobbing experiences compared to those who had never considered resigning (p = 0.008), e) who had been punished for reporting a bullying/mobbing incident compared to those who had not (p = 0.001), and f) who considered the incident unimportant to be reported compared to those who avoided reporting due to other causes (p = 0.048). This data highlights the need to establish effective and safe procedures for bullying/mobbing reporting, aiming to support bulling/mobbing victims and witnesses, and further to protect their legal rights. Both victims and witnesses of workplace bullying/mobbing need to be assessed by mental health professionals for PTSD symptoms in order to have access to effective treatment.
Keywords: Cyprus; ICU; PTSD; Bullying; Emergency; Mental health; Trauma; Workplace incivility